Chemo-mechanical expansion of lithium electrode materials – on the route to mechanically optimized all-solid-state batteries. Issue 8 (7th June 2018) - Koerver, Raimund; Zhang, Wenbo; de Biasi, Lea; Schweidler, Simon; Kondrakov, Aleksandr O.; Kolling, Stefan; Brezesinski, Torsten; Hartmann, Pascal; Zeier, Wolfgang G.; Janek, Jürgen
Abstract : The volume effects of electrode materials can cause local stress development, contact loss and particle cracking in the rigid environment of a solid-state battery. Abstract : Charge and discharge of lithium ion battery electrodes is accompanied by severe volume changes. In a confined space, the volume cannot expand, leading to significant pressures induced by local microstructural changes within the battery. While volume changes appear to be less critical in batteries with liquid electrolytes, they will be more critical in the case of lithium ion batteries with solid electrolytes and they will be even more critical and detrimental in the case of all-solid-state batteries with a lithium metal electrode. In this work we first summarize, compare, and analyze the volume changes occurring in state of the art electrode materials, based on crystallographic studies. A quantitative analysis follows that is based on the evaluation of the partial molar volume of lithium as a function of the degree of lithiation for different electrode materials. Second, the reaction volumes of operating full cells ("charge/discharge volumes") are experimentally determined from pressure-dependent open-circuit voltage measurements. The resulting changes in the open-circuit voltage are in the order of 1 mV/100 MPa, are well measurable, and agree with changes observed in the crystallographic data. Third, the pressure changes within solid-state batteries are approximated under the assumption of incompressibility, i.e. for constant volume of the cell casing, and are compared to experimental data obtained from model-type full cells. In addition to the understanding of the occurring volume changes of electrode materials and resulting pressure changes in solid-state batteries, we propose "mechanical" blending of electrode materials to achieve better cycling performance when aiming at "zero-strain" electrodes.